Competency development of southern African housing officers (Journal of Student Affairs in Africa, 2021)
The Report on the Ministerial Committee for the Review of the Provision of Student Housing at South African Universities (Department of Higher Education and Training, 2011) has provided a comprehensive review of residences across several housing functional areas. In one of the residence management and administration recommendations it stated, “The professionalisation of housing staff is an urgent priority” (p. 141). This coupled with the report’s estimated “current residence bed shortage of approximately 195 815 beds […] with a cost of overcoming this shortage over a period of ten years is estimated at R82.4 billion” (pp. xvii–xviii) will mean the hiring and training of hundreds of housing professional staff to meet not only the demand of the additional residence beds but the training of current housing staff. In 2010 The Association of College and University Housing Officers – International Southern Africa Chapter (ACUHO-I SAC) initiated a Student Housing Training Institute (SHTI) first held in 2011 to meet the demands for professionalising housing staff. The SHTI was organised using a competency development model first used to develop the Association of College and University Housing Officers –International (ACUHO-I) James C. Grimm National Housing Training Institute (NHTI) held in the US.
Keywords: competency; development; housing officers; higher education; professionalisation